PUBLIC DEBT AND ECONOMIC GROWTH IN INDONESIA - Bakri, Muhammad Rafi; Adiwicaksana, Yohanes Rama; Utami, Anastasya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study analyzes the impact of government debt contributed to the economic growth in Indonesia over the period 2005 to 2020. We employ the ordinary least square (OLS) approach to see if other factors like government funding, government investment, inflation, and budget spending have an effect on economic growth. The findings show that government debt does not have a significant effect on economic growth in Indonesia. The results indicate that government debt over time has a negative impact on GDP. Furthermore, we discovered that government investment and the rate of inflation are decreasing functions of GDP.